Factors contributing to sepsis-associated encephalopathy: a comprehensive systematic review and meta-analysis - Zhang, Zhiyang; Guo, Li; Jia, Lijing; Duo, Hong; Shen, Limin; Zhao, Heling (Frontiers in Medicine, 2024)
Background: This study aims to systematically assess the risk factors, the overall strength of association, and evidence quality related to sepsis-associated encephalopathy.Methods: A systematic search was conducted in the Cochrane Library, PubMed, Web of Science, and Embase for cohort or case-control studies published up to August 2023 on risk factors associated with sepsis-related encephalopathy. The selected studies were screened, data were extracted, and the quality was evaluated using the Newcastle-Ottawa Scale. Meta-analysis was performed using RevMan 5.3 software. The certainty of the evidence was assessed using the GRADE criteria.Results: A total of 13 studies involving 1,906 participants were included in the analysis.Among these studies, 12 were of high quality, and one was of moderate quality. Our meta-analysis identified six risk factors significantly associated with Serious Adverse Events (SAE). These included APACHE II, SOFA, Age, Tau protein, and IL-6, which were found to be risk factors with significant effects (Standard Mean Difference SMD:1.24-2.30), and Albumin, which was a risk factor with moderate effects (SMD: -0.55).However, the certainty of evidence for the risk factors identified in this meta-analysis ranged from low to medium.This systematic review and meta-analysis identified several risk factors with moderate to significant effects. APACHE II, SOFA, Age, Tau protein, IL-6, and Albumin were associated with sepsis-related encephalopathy and were supported by medium-to high-quality evidence. These findings provide healthcare professionals with an evidence-based foundation for managing and treating hospitalized adult patients with sepsis-related encephalopathy.